Managing herbicide resistance in China. Issue 1 (1st January 2021) - Liu, Xiangying; Merchant, Austin; Xiang, Shihai; Zong, Tao; Zhou, Xuguo; Bai, Lianyang
Abstract: Since its initial introduction in the late 1950s, chemical control has dominated weed management practices in China. Not surprisingly, the development of herbicide resistance has become the biggest threat to long-term, sustainable weed management in China. Given that China has followed the same laissez-faire approach toward resistance management that has been practiced in developed countries such as the United States, herbicide resistance has evolved rapidly and increased steadily over the years. Previously, we carried out a systematic review to quantitatively assess herbicide-resistance issues in China. In this review, our main objective is to focus on mechanistic studies and management practices to document the (1) history of herbicide application in China; (2) resistance mechanisms governing the eight most resistance-prone herbicide groups, including acetolactate synthase inhibitors, acetyl-CoA carboxylase inhibitors, synthetic auxin herbicides, 5-enolpyruvylshikimate-3-phosphate synthase inhibitors, protoporphyrinogen oxidase inhibitors, photosystem I electron diverters, photosystem II inhibitors, and long-chain fatty-acid inhibitors; and (3) herbicide-resistance management strategies commonly used in China, including chemical, cultural, biological, physical, and integrated approaches. At the end, perspectives and future research are discussed to address the pressing need for the development of integrated herbicide-resistance management in China.